2016
DOI: 10.1002/pca.2618
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Alkaloids in Stephania hainanensis by Liquid Chromatography Coupled with Quadrupole Time‐of‐flight Mass Spectrometry

Abstract: The LC-QTOF-MS/MS method enabled profiling and rational, but tentative, identification of diverse alkaloids in Stephania hainanensis. The results obtained may be helpful for understanding the bioactivity of S. hainanensis and evaluating the quality of this plant. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 20 publications
(71 reference statements)
1
40
0
Order By: Relevance
“…steporphine, ushinsunine, fibrecisine and roemeroline. Considering the hydroxy group present at C‐4 or C‐7 could easily be eliminated to form the intense [M + H−H 2 O] + ion at m/z 278.1187, compound 37 was tentatively identified as steporphine with the OH at C‐4 and/or ushinsunine with the OH at C‐7 (Semwal et al ., ; He et al ., ). The OH of compound 48 , however, was difficult to dissociate, and thus this compound was tentatively deduced as fibrecisine with the OH at C‐8 and/or roemeroline with the OH at C‐9 (Zhang and Rao, ; Semwal et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…steporphine, ushinsunine, fibrecisine and roemeroline. Considering the hydroxy group present at C‐4 or C‐7 could easily be eliminated to form the intense [M + H−H 2 O] + ion at m/z 278.1187, compound 37 was tentatively identified as steporphine with the OH at C‐4 and/or ushinsunine with the OH at C‐7 (Semwal et al ., ; He et al ., ). The OH of compound 48 , however, was difficult to dissociate, and thus this compound was tentatively deduced as fibrecisine with the OH at C‐8 and/or roemeroline with the OH at C‐9 (Zhang and Rao, ; Semwal et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The split of the [M + H] + ion led to the base peak fragment ion at m/z 107.0492, 30 Da lower than of compound 5 , thus indicating the presence of only one hydroxyl group on ring C. If the OH group was at C‐11, compound 8 could be identified as norcanelilline . However, if the OH group was at C‐12, compound 8 would be coclaurine or norjuziphine . According to data in the literature, benzylisoquinoline alkaloids without an oxygen functional group at C‐11 show benzyl fragments as the most intense fragment ions, which is due to their lesser ability to stabilise the benzyl leaving group .…”
Section: Resultsmentioning
confidence: 99%
“…15 However, if the OH group was at C-12, compound 8 would be coclaurine or norjuziphine. 16,17 According to data in the literature, benzylisoquinoline alkaloids without an oxygen functional group at C-11 show benzyl fragments as the most intense fragment ions, which is due to their lesser ability to stabilise the benzyl leaving group. 14…”
Section: Benzylisoquinoline Alkaloidsmentioning
confidence: 99%
“…Alkaloids from Papaver species possess significant biological activity [13,15], and the alkaloid content of Papaver plants varies greatly depending on their growth stage, conditions, and origin [4,12,16]. Rapid and reliable analytical techniques must be developed to facilitate identification and structural determination of alkaloids in complex extracts and medicine herbs [17][18][19][20][21][22][23]. To discover medicinally relevant compounds and potential alternatives to plants as the commercial source of valuable BIAs, metabolomic studies of the Papaver species have been reported by metabolomics with chemometric approaches and transcript profiling [13,15,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%